2016
DOI: 10.1002/asna.201612428
|View full text |Cite
|
Sign up to set email alerts
|

Observations of solar X‐ray and EUV jets and their related phenomena

Abstract: Solar jets are fast‐moving, elongated brightenings related to ejections seen in both images and spectra on all scales from barely visible chromospheric jets to coronal jets extending up to a few solar radii. The largest, most powerful jets are the source of type III radio bursts, energetic electrons and ions with greatly enhanced 3He and heavy element abundances. The frequent coronal jets from polar and equatorial coronal holes may contribute to the solar wind. The primary acceleration mechanism for all jets i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 90 publications
(137 reference statements)
0
45
0
Order By: Relevance
“…Solar coronal jets are narrow, short-lived coronal features that occur frequently throughout the entire solar magnetic cycle (Shimojo et al 1998;Wang et al 1998;Savcheva et al 2007;Hong et al 2011;Raouafi et al 2016). These events have been observed in all regions of the solar surface: in active regions (Shibata et al 1992;Innes et al 2011;Panesar et al 2016;Sterling et al 2016Sterling et al , 2017, quiet regions (Hong et al 2011;Innes et al 2016), and coronal holes Nisticò et al 2009;Pucci et al 2013;Sterling et al 2015;Panesar et al 2018). In addition to being wide-spread across the solar surface, they also occur very frequently; Savcheva et al (2007) found that jets in polar coronal holes occur at an average rate of 60 jets per day.…”
Section: Introductionmentioning
confidence: 98%
“…Solar coronal jets are narrow, short-lived coronal features that occur frequently throughout the entire solar magnetic cycle (Shimojo et al 1998;Wang et al 1998;Savcheva et al 2007;Hong et al 2011;Raouafi et al 2016). These events have been observed in all regions of the solar surface: in active regions (Shibata et al 1992;Innes et al 2011;Panesar et al 2016;Sterling et al 2016Sterling et al , 2017, quiet regions (Hong et al 2011;Innes et al 2016), and coronal holes Nisticò et al 2009;Pucci et al 2013;Sterling et al 2015;Panesar et al 2018). In addition to being wide-spread across the solar surface, they also occur very frequently; Savcheva et al (2007) found that jets in polar coronal holes occur at an average rate of 60 jets per day.…”
Section: Introductionmentioning
confidence: 98%
“…Coronal jets are collimated plasma ejections that occur repeatedly everywhere on the Sun and may contribute a significant amount of mass and energy to the corona and solar wind (Patsourakos et al 2008;Moore et al 2010;Raouafi et al 2010;Sterling et al 2015;Innes et al 2016;Raouafi et al 2016). Recurrent jets often are ejected from coronal bright points throughout their lifetimes of hours to days (Kumar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They occur in different solar environments over a broad range of temporal and spatial scales (Cirtain et al 2007;Moore et al 2010;Innes et al 2016). Coronal jets typically show a brighten- navdeep.k.panesar@nasa.gov ing at an edge of their base (called the jet-base bright point, JBP) and a bright spire.…”
Section: Introductionmentioning
confidence: 99%